The Analysis of Bekasi Industrial Tourism's Brand Awareness - Kristian Sulistio; Yunita Ismail (FIRM Journal of Management Studies, 2018)
As the part of tourism development of Bekasi, Tourism Office of Bekasi Regency has a target to bring 2 million tourists to Bekasi in 2018. Bekasi Regency itself is the largest industrial park in Southeast Asia with the estimated 4000 industries. Seeing this potential, Tourism Office of Bekasi Regency and Jababeka form a concept called Bekasi Industrial Tourism. This study aimed to analyze the most effective promotion strategies in creating the brand awareness of Bekasi Industrial Tourism. This research used a quantitative research method to evaluate the independent variables (Advertising, Personal Selling and Social Media Marketing) towards dependent variable (Brand Awareness). Non-probability sampling with purposive sampling was used in this study. Questionnaires consisting of 21 questions with the Likert scale as a tool to measure the level of agreement was distributed to 125 respondents. Data analysis used in this research were validity, reliability, classical assumption and multiple regression. The result affirmed that advertising, personal selling, and social media marketing have a partial significant influence on brand awareness. Social media marketing has the highest influence on brand awareness followed by personal selling and advertising. This study also showed that all independent variables (advertising, personal selling, and social media marketing) have simultaneous significant influence towards brand awareness with 75% of adjusted R2.